ANALYSIS OF THE POSSIBILITY OF USING EXHAUST GAS COMPOSITION IN THE DIAGNOSIS OF A DIESEL ENGINE - Patrycja Puzdrowska; Wiktoria Nowicka (Scientific Journal of Gdynia Maritime University, 2025)
The article analyzes the impact of malfunctions in compression-ignition engine systems on exhaust composition and cycle parameters. A naturally aspirated, single-cylinder, four-stroke Farymann Diesel D10 engine was studied, with simulated common failures. The research included laboratory experiments and computer simulations using DIESEL-RK, a tool for optimizing engine processes and thermodynamic cycles.